2002
DOI: 10.1038/sj.bjp.0704814
|View full text |Cite|
|
Sign up to set email alerts
|

Renal targeting of captopril selectively enhances the intrarenal over the systemic effects of ACE inhibition in rats

Abstract: 1 In previous studies on the renal targeting of the ACE inhibitor captopril, we demonstrated that a 6 fold increased concentration of this drug could be obtained in the kidney after conjugation to the low-molecular-weight protein lysozyme. In this study, we investigated in unrestrained rats whether systemic administration of captopril ± lysozyme also results in an enhanced e ect on renal parameters, relative to the systemic e ects.2 Renal e ects: intravenous infusion of captopril ± lysozyme for 6 h resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 47 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…The ACE inhibitor captopril has also been conjugated with lysozyme via a disulfide bond and using succinimidyloxycarbonyl- α -methyl- α -(2-pyridyldithio) toluene (SMPT) as a linker 18,19 . Research showed captopril could be released from the conjugate either enzymatically by β -lyase and/or non-enzymatically by thiol-disulfide exchange with endogenous thiols.…”
Section: Strategiesmentioning
confidence: 99%
“…The ACE inhibitor captopril has also been conjugated with lysozyme via a disulfide bond and using succinimidyloxycarbonyl- α -methyl- α -(2-pyridyldithio) toluene (SMPT) as a linker 18,19 . Research showed captopril could be released from the conjugate either enzymatically by β -lyase and/or non-enzymatically by thiol-disulfide exchange with endogenous thiols.…”
Section: Strategiesmentioning
confidence: 99%
“…The renal proximal tubular cell, triggered by long-term exposure to proteins, is believed to play a pivotal role in the cascade of pathophysiological processes towards end-stage renal failure (ESKD) 1, which is irreversible and permanent. As the pathogenic condition becomes worse, renal replacement therapy (RRT), such as dialysis or renal transplantation, has to be applied to sustain the lives of patients.…”
Section: Introductionmentioning
confidence: 99%